Pembelajaran Daring Melalui Whatsapp Dalam Capaian Kehadiran, Aktivitas Belajar Dan Hasil Belajar di Masa Pandemi - Sriyanti, Sriyanti; Indrawari, Karliana; Munawaroh, Ayu (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
The purpose of this study was to determine learning, student learning experiences and learning activities and online learning outcomes through WhatsApp, This type of research uses qualitative research. data collection with the method of observation, interviews, and documentation. The results of the study show that online learning at the PAI Study Program, Muhammadiyah University of Palembang uses the WA application, Google meeting, zoom, and google classroom. lecturer in PAI Study Program Achievement of student attendance in online learning from 100 percent, 90 percent, even 80 percent. active in learning. Learning outcomes are said to be good by showing that students know, understand, like, and are satisfied during the learning process.